ANALISIS PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HELM MEREK KYT ( Studi Di Kecamatan Gajah Mungkur Kota Semarang) - Alex Leo Fernando Malau, 10.05.51.0023; Indriyaningrum, Kis (Students Journal of Economic and Management, 2014)
This study analyzed the influence of brand image and product quality on purchase decisions. Object of study in this paper is the consumers who buy and use the brand KYT helmet in District Gajah Mungkur Semarang City. The sample used in this study were 100 respondents with a sampling technique is the method of purposive sampling, the sampling of carefully selected by taking the object of research is selective and has specific characteristics. The data used are primary data, analysis of data used include test validity, reliability testing, multiple linear regression, the coefficient of determination and hypothesis testing which includes the F test and t test. Based on data analysis and hypothesis testing showed that brand image in partial positive and significant impact on purchasing decisions KYT helmet brand. Variable quality products and a significant positive influence on purchasing decisions KYT helmet brand. The test results of determination unknown variables brand image and product quality can explain the variation of 65.7% on purchasing decisions KYT helmet brand, while the remaining 34.3% is influenced by other variables that were not analyzed in this study.Keywords: Brand Image, Product Quality and Purchase Decision